Strategi Komunikasi Indonesian Ocean Pride dalam Pengurangan Sampah Plastik di Indonesia (LITERATUS, 2023)
Plastic is a material that is frequently utilized to create goods that satisfy human requirements. Although plastic has many advantages, it can also have a significant negative impact if it is not used and utilized properly because it is a non-organic waste (Nirmalasari, 2021). This adverse effect happens as a result of how long it takes the planet to break down garbage composed of plastic-based products—even tens to hundreds of years. Plastic is frequently consumed by marine life since it is thought to be food that could affect their ability to digest it. In order to conserve Indonesia's oceans, Indonesia Ocean Pride is an environmentalist group that uses the 4R campaign—reduce, reuse, recycle, and replace—to educate the majority of people. The research aimed to discover more concerning the communication strategy used by Indonesia Ocean Pride to cut down on plastic trash there. The approach taken is descriptive-qualitative, utilizing tools for data collecting like observation, interviews, and documentation as well as the idea of campaign communication strategy. This study demonstrates that Indonesia Ocean Pride management uses a campaign communication approach that comprises proclaiming, inspiring, instructing, and informing (information dissemination). Because so many people are still unaware of the risks associated with using plastic for environmental sustainability, Indonesia Ocean Pride is continuing to advocate for reducing the use of plastic waste in Indonesia.